Sexual Dimorphism in Hepatocyte Xenograft Models. (29th April 2021) - Sari, Gulce; van Oord, Gertine W.; van de Garde, Martijn D.B.; Voermans, Jolanda J.C.; Boonstra, Andre; Vanwolleghem, Thomas
Humanized liver mouse models are crucial tools in liver research, specifically in the fields of liver cell biology, viral hepatitis and drug metabolism. The livers of these humanized mouse models are repopulated by 3-dimensional islands of fully functional primary human hepatocytes (PHH), which are notoriously difficult to maintain in vitro. As low efficiency and high cost hamper widespread use, optimization is of great importance. In the present study, we analyzed experimental factors associated with Hepatitis E virus (HEV) infection and PHH engraftment in 2 xenograft systems on a Nod-SCID-IL2Ry -/- background: the alb- urokinase plasminogen activator mouse model (uPA-NOG, n=399); and the alb- HSV thymidine kinase model (TK-NOG, n = 198). In a first analysis, HEV fecal shedding in liver humanized uPA-NOG and TK-NOG mice with comparable human albumin levels was found to be similar irrespective of the mouse genetic background. In a second analysis, sex, mouse age at transplantation and hepatocyte donor were the most determinant factors for xenograft success in both models. The sexual imbalance for xenograft success was related to higher baseline ALT levels and lower thresholds for ganciclovir induced liver morbidity and mortality in males. These data call for sexual standardization of human hepatocyte xenograft models, but also provide a platform for further studies on mechanisms behind sexual dimorphism in liver diseases.